2007
DOI: 10.1111/j.1365-2958.2007.05898.x
|View full text |Cite
|
Sign up to set email alerts
|

mgpB and mgpC sequence diversity in Mycoplasma genitalium is generated by segmental reciprocal recombination with repetitive chromosomal sequences

Abstract: SummaryMycoplasma genitalium is associated with sexually transmitted infections in men and women that, if untreated, can persist, suggesting that mechanism(s) exist to facilitate immune evasion. Approximately 4% of the limited M. genitalium genome contains repeat sequences termed MgPar regions that have homology to mgpB and mgpC, which encode antigenic proteins associated with attachment. We have previously shown that mgpB sequences vary within a single strain of M. genitalium in a pattern consistent with reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
130
3
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(145 citation statements)
references
References 86 publications
(156 reference statements)
10
130
3
2
Order By: Relevance
“…Still, no sequence variability within this region has been observed with M. pneumoniae (37). In contrast to the recent findings of extensive sequence variability in M. genitalium (17,18,27,34), the existence of two highly conserved types of M. pneumoniae P1 gene sequences has been demonstrated repeatedly (9). The existence of these two types of the P1 gene (type 1 and type 2) was shown to be an excellent marker for numerous other variations within their genomes, some of which likely lead to virulence differences observed among strains (8).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Still, no sequence variability within this region has been observed with M. pneumoniae (37). In contrast to the recent findings of extensive sequence variability in M. genitalium (17,18,27,34), the existence of two highly conserved types of M. pneumoniae P1 gene sequences has been demonstrated repeatedly (9). The existence of these two types of the P1 gene (type 1 and type 2) was shown to be an excellent marker for numerous other variations within their genomes, some of which likely lead to virulence differences observed among strains (8).…”
Section: Discussioncontrasting
confidence: 50%
“…Extensive sequence variability resulting from recombination between repetitive elements of mgpB and MgPars was recently confirmed with reference strain G37 as well as with clinical strains (17,18,27). However, the MgPa-13 region (nucleotides 181 to 460) does not share homology with other regions in the G37 genome, and this region was chosen for development of a conventional diagnostic PCR assay (22).…”
Section: Discussionmentioning
confidence: 99%
“…After evaluation of the specimens, two of these six VNTR loci were rejected due to lack of adequate discrimination and four VNTR loci were finally chosen for further assessment. Three TR loci, MG307-STR, MG309-STR, and MG338-STR, were named according to a previous study (Ma et al, 2008), and the fourth TR locus, previously identified (Iverson-Cabral et al, 2007) but never used in a typing scheme, was named Mge1.…”
Section: Methodsmentioning
confidence: 99%
“…Three of the four VNTRs were located in LPencoding loci (MG307-STR, MG309-STR and MG338-STR) and had been previously described (Ma et al, 2008). Mge1, previously identified by Iverson-Cabral et al (2007), was located in the mgpB locus, which encodes the main adhesin MG191 (Burgos et al, 2006) (Table 2). The MG309-STR and MG338-STR markers were the most discriminatory VNTRs, with 15 and 13 different alleles, respectively.…”
Section: Mlva Typingmentioning
confidence: 99%
“…4). In some instances SGC can be simple: in cases where the 3′ boundary of gene conversion occurs within the coding sequence, SGC causes only the part of the gene encoding the exposed N-terminal domain of the antigen to be exchanged ("3′ donation") (124), a process similar to the exchange of antigen variable region "cassettes" by pathogens such as Anaplasma marginale (184), Treponema pallidum (185), and Mycoplasma genitalum (186)(187)(188). In addition, SGC can form a "mosaic" VSG, exchanging segments across the gene and introducing variation into the antigenically-important N-terminal domain.…”
Section: Segmental Gene Conversion Produces Functional Vsg Surface Coatsmentioning
confidence: 99%